2017
DOI: 10.1111/1750-3841.13788
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study Between Labeling and Reality: The Case of Phytochemical Composition of Commercial Pomegranate‐Based Products

Abstract: Manufacturers are deeply involved in the development of new pomegranate-based products, which have acquired great prestige due to many studies proving their potential health benefits. Commercial pomegranate products including capsules and supplements and juices and nectars were assayed. The contents of the key phytochemical compounds (punicalagin, ellagic acid, and total polyphenolic content) and the associated antioxidant capacity (DPPH , ABTS , and FRAP) were analyzed. The experimental ranges of punicalagin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 32 publications
2
3
0
Order By: Relevance
“…Regarding the almond skin, the TPC and antioxidant activity (ABTS and DPPH) were not affected by the irrigation treatments, except for FRAP method, which showed that T2 was similar to the control and T4 had the lowest antioxidant activity. These results agreed with Cano Lamadrid et al [32] and Sánchez-Rodríguez et al [12] in studies investigating effects of deficit irrigation on quality and functional profiles of table olives (hydroSOStainable olives) and pomegranates, respectively [9,12,33]. An increase, however, in polyphenols and antioxidant activity was observed for lettuce growing under water stress conditions [34] and grapes from clusters exposed to RDI (compared with SDI), which might happen due to the reduction of canopy leaf area of vines under RDI conditions [35].…”
Section: Resultssupporting
confidence: 93%
“…Regarding the almond skin, the TPC and antioxidant activity (ABTS and DPPH) were not affected by the irrigation treatments, except for FRAP method, which showed that T2 was similar to the control and T4 had the lowest antioxidant activity. These results agreed with Cano Lamadrid et al [32] and Sánchez-Rodríguez et al [12] in studies investigating effects of deficit irrigation on quality and functional profiles of table olives (hydroSOStainable olives) and pomegranates, respectively [9,12,33]. An increase, however, in polyphenols and antioxidant activity was observed for lettuce growing under water stress conditions [34] and grapes from clusters exposed to RDI (compared with SDI), which might happen due to the reduction of canopy leaf area of vines under RDI conditions [35].…”
Section: Resultssupporting
confidence: 93%
“…On the other hand, TPC was positively correlated with PC as Türkyılmaz, Tağı, Dereli, and Özkan () reported; the total phenolic compounds of Pom juices significantly correlated with the PC ( R = 0.94; p < 0.005). Moreover, Pearson correlation showed that the correlation of TPC was affected by EA content, as mentioned in previous research (Borges et al., ; Cano‐Lamadrid et al., ). On the contrary, Todaro et al.…”
Section: Resultssupporting
confidence: 75%
“…() reported that Sicilian and Spanish pomegranates (sweet cultivars such as Dente di cavallo , Violetto , Mollar de Elche , Valenciana ) presented TA from 1.3 to 2.5 g citric acid/L. Besides, there are high differences in TA between sweet and sour cultivars; for instance, Mollar de Elche juice has a mean value of 1.51 g citric acid/L while Wonderful juice had a TA value of 7.32 g citric acid/L (Cano‐Lamadrid, Lipan, Calín‐Sánchez, Hernández, & Carbonell‐Barrachina, ). Therefore, most of the studied samples were probably made from a blend of cultivars.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations